1995
DOI: 10.1016/0277-9536(95)00058-f
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions and attitudes about informed consent in clinical research involving children

Abstract: We interviewed 64 parents by questionnaire after completion of a clinical trial involving their children for their perceptions and attitudes about informed consent. The results show that only a small minority realized that drug trials are designed to assess not only efficacy but safety as well. More worrisome was the majority of parents who felt that drug trials conducted by hospitals are of no or low risks. Moreover, a significant minority offered the view that the strict informed consent procedures we follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 37 publications
2
82
0
3
Order By: Relevance
“…This suggests that many parents have considerable trust in their physicians, and would depend on the physician to act with the infant's best interests in mind, which is consistent with previous studies 18 and underscores the vulnerability of parents to physician beliefs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This suggests that many parents have considerable trust in their physicians, and would depend on the physician to act with the infant's best interests in mind, which is consistent with previous studies 18 and underscores the vulnerability of parents to physician beliefs.…”
Section: Discussionsupporting
confidence: 84%
“…A very interesting finding in this study was that almost a third of both parent groups would consent to enroll their infant in a study 18 that a large percentage of parents volunteering their infant for a clinical trial did not understand that there were risks associated with participation. It has also been found that parents consenting for their infants participation were found to be more emotionally and socially disadvantaged than parents refusing consent.…”
Section: Discussionmentioning
confidence: 90%
“…31,32,55,65 However, the relationship between anxiety, vulnerability and trial decisions may be mediated or moderated by factors such as trust in medical research 66 and the parent-practitioner relationship. 23,56,[67][68][69][70] The practicalities of trial participation are less commonly mentioned; 71 this may reflect the fact that most studies have been conducted in neonatology and oncology, when the child is usually in hospital at the time of the trial approach.…”
Section: Influences On Parents' Decision To Enter Their Child Into a mentioning
confidence: 99%
“…24 In another study of parents consenting to a randomized trial on behalf of their children, neither the need to assess safety as well as ef®cacy, or the right to withdraw from the study were widely appreciated and many parents expressed the opinion that informed consent was unnecessary, as they would trust the advice of the doctor. 25 There has been little research amongst adults considering trial participation themselves, examining understanding of the manner in which randomized trials are conducted, or the impact of patients' attitudes towards randomized trials on willingness to participate. These issues are important in order to improve doctor-patient communication about clinical trials.…”
Section: Introductionmentioning
confidence: 99%